The Medicago truncatula Sugar Transport Protein 13 and Its Lr67res-Like Variant Confer Powdery Mildew Resistance in Legumes via Defense Modulation. (8th February 2021) - Gupta, Megha; Dubey, Shubham; Jain, Deepti; Chandran, Divya
Abstract: Obligate biotrophic pathogens like the pea powdery mildew© (PM) Erysiphe pisi establish long-term feeding relationships with their host, during which they siphon sugars from host cells through haustoria. Plants in turn deploy sugar transporters to restrict carbon allocation toward pathogens, as a defense mechanism. Studies in Arabidopsis have shown that sugar transport protein 13 (STP13), a proton-hexose symporter involved in apoplasmic hexose retrieval, contributes to bacterial and necrotrophic fungal resistance by limiting sugar flux toward these pathogens. By contrast, expression of Lr67res, a transport-deficient wheat STP13 variant harboring two amino acid substitutions (G144R and V387L), conferred resistance against biotrophic fungi in wheat and barley, indicating its broad applicability in disease management. Here, we investigated the role of STP13 and STP13 G144R in legume–PM interactions. We show that Medicago truncatula STP13.1 is a proton-hexose symporter involved in basal resistance against PM and indirectly show that Lr67res -mediated PM resistance, so far reported only in monocots, is transferable to legumes. Among the 30 MtSTP s, STP13.1 exhibited the highest fold induction in PM-challenged leaves and was also responsive to chitosan, ABA and sugar treatment. Functional assays in yeast showed that introduction of the G144R mutation but not V388L abolished MtSTP13.1's hexose uptake ability. Virus-induced gene silencing of MtSTP13 repressed pathogenesis-related ( PR ) gene expression and enhanced PM susceptibility in M. truncatula whereas transient overexpression of MtSTP13.1 or MtSTP13.1 G144R in pea induced PR and isoflavonoid pathway genes and enhanced PM resistance. We propose a model in which STP13.1-mediated sugar signaling triggers defense responses against PM in legumes.